Thomas Hardy's legal fictions - Ferguson, Trish (Trinity College (Dublin, Ireland). School of English, 2008)
The objective of this thesis is to demonstrate that Hardy’s role as a magistrate had a pervasive effect on his development of the tragic novel and to argue that legal issues are integral to the narrative pattern of his tragic plots, which involves the legal marginalization of the tragic protagonist. I argue that Hardy constructed his tragic fiction through presenting legal issues, primarily to reflect the contemporary position of legally disenfranchised elements of society, namely, agricultural labourers and women. Hardy’s legal plots also highlight flaws in the newly-reformed judicial system. Although his novels engage with and critique contemporary legal reforms long after they had been implemented by a series of legislative acts, Hardy’s tragic novels highlight many contemporary socio-economic and legal issues still in need of reform for the benefit of those marginalized by the law. Hardy’s critique of the law is also rendered through the carnivalesque depiction of the newly-developed constabulary and trial procedure in The Mayor of Casterbridge. I also demonstrate that pseudo-trial scenes take place in the domestic realm in many of the novels, as Hardy engages with the debate surrounding the newly-implemented provision of legal defence counsel in metaphorical trial scenes. Drawing on theory from the interdisciplinary study of Literature and the Law, I demonstrate that Hardy’s narratives mirror defence counsel, providing a counter-discourse, which opposes and subverts that of civic law. Finally, this thesis finds that the deaths in Hardy’s tragic novels are suicides resulting from the tragic character’s legal marginalization and that his novels thus function as a critique of the elitist and reductive nature of the operation of the law.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin